The Effect Of Comic Books To Improve Reading Comprehension Ability At Grade VIII At SMP N 12 Pematangsiantar - Indra Jayanti Damanik; Grace Sari Harianja (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
This study was aimed at investigating whether“Does comic books effect to improve student’s reading comprehension skill of narrative text at grade VIII SMP N 12 Pematangsiantar?”This research was a quantitative approach. For the data collection, there werePre-test and Post-test. The population of this study was the students the Eighth grade of SMP N 12 Pematangsiantar has 5 classes which of 184 studentswith a sample50 students. The data analysis started fromscoring composition and finding average of the score.Based on the data analysis the researcher finding also provedthe Score Pre-test of Control is 1308 and for average of control class is 52, 32. The Score Post-test of Control Classis 1484 and for average of control class is 59, 36. The Score Pre-test of Experimental Classis 1448 and for average of control class is 57, 92.The Score Post-test of Experimental Class is2060and for average of control class is 82,4